Study of Organo- Phosphorous Compound Poisonings with Blood Sugar Levels in Telangana Population - Jakaregari Srinivas (Indian Journal of Forensic Medicine & Toxicology, 2020)
85 adult patients aged between 23 to 60 years of age were admitted at emergency wards were studied. These patients were known diabetic since 2 to 5 years, The clinical manifestation were 6(7.0%) had anxiety, 7(8.23%) had giddiness, 5(5.88%) had emotional liability 7(8.23%) had slurred speech 4(4.70%) had ataxia, 9(10.5%) had drowsiness, 5(5.88%) had confusion 6(7.0%) had headache, 8(9.41%) had coma, 6(7.0%) had absence of reflexes, 12(14.1%) had dyspnea, 10(11.7%) had hypotension. The random blood sugar level in 48(56.4%) had 60-200 mg% and 37(43.5%) had > 200 mg% This pragmatic approach to patients of oregano phosphorus patients who were diabetic and under anti diabetic treatment will be quite useful to physician and medico- legal expert to treat efficiently to avoid morbidity and mortality in Diabetic patients because diabetic mellitus is a silent killer and challenge to the clinicians globally.